International benchmarking of electricity distribution utilities - Finn R. Førsund; Dag Fjeld Edvardsen (University of Oslo, Department of Economics, 2001)
Benchmarking by means of applying the DEA model is appearing as an interesting alternative for regulators under the new regimes for electricity distributors. A sample of large electricity distribution utilities from Denmark, Finland, Norway, Sweden and the Netherlands for the year 1997 is studied by assuming a common production frontier for all countries. The peers supporting the benchmark frontier are from all countries. New indexes describing cross country connections between peers and their inefficient units are developed, as well as productivity measurements between units from different countries.
Keywords: C43; C61; D24; L94; 330; Electricity utility; benchmarking; efficiency; DEA; Malmquist productivity index; Benchmarking; Elektrizitätswirtschaft; Data-Envelopment-Analyse; Niederlande; Dänemark; Norwegen; Schweden; Finnland